"Piracy" - Arlen, Michael, 1895-1956 (Salt Lake City, UT : Project Gutenberg, 2024)
"Piracy: A Romantic Chronicle of These Days" by Michael Arlen is a novel written in the early 20th century. The story centers around Ivor Pelham Marlay, a complex character grappling with feelings of loneliness and introspection as he navigates life in post-war London. The narrative appears to explore themes of love, identity, and societal expectations, reflecting the cultural shifts of the era. At the start of the novel, we are introduced to Ivor Marlay, who sits alone at Mont Agel restaurant on the night of May 1, 1921. Engaged in deep contemplation, he reflects on his life, including the weight of his recent expulsion from school and the loss of his arm during the war. As he interacts with M. Stutz, the owner of the restaurant, Ivor's internal struggles about self-worth and belonging come to light. His loneliness is palpable, and despite being financially free, he grapples with the existential dread that accompanies such freedom, suggesting an ongoing quest for connection and purpose amidst the superficial glamor and chaos of London society. (This is an automatically generated summary.)
Release date is 2024-06-05
Chuck Greif and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Rich people -- Fiction; Man-woman relationships -- Fiction; Novelists -- Fiction; London (England) -- Social life and customs -- 20th century -- Fiction